2020
DOI: 10.1002/1873-3468.13748
|View full text |Cite
|
Sign up to set email alerts
|

Receptor‐Interacting Protein Kinase 3 (RIPK3) inhibits autophagic flux during necroptosis in intestinal epithelial cells

Abstract: Autophagy is an intracellular process that regulates the degradation of cytosolic proteins and organelles. Dying cells often accumulate autophagosomes. However, the mechanisms by which necroptotic stimulation induces autophagosomes are not defined. Here, we demonstrate that the activation of necroptosis with TNF-a plus the cell-permeable pan-caspase inhibitor Z-VAD induces LC3-II and LC3 puncta, markers of autophagosomes, via the receptor-interacting protein kinase 3 (RIPK3) in intestinal epithelial cells. Sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 30 publications
1
12
0
Order By: Relevance
“…This resource management system, otherwise known as autophagy, helps maintain homeostasis and can promote cell survival during stress (147). Several studies investigating a role for autophagy during necroptotic signaling have showed increased lipidated LC3 (microtubuleassociated proteins 1A/1B light chain 3B) and other markers of autophagosomes during TNF-induced necroptosis (119,136,148,149). However, this accumulation of autophagosomes is not thought to be due to the stimulation of autophagy during necroptosis but rather due to a failure of autophagosomes to undergo proper lysosomal degradation (119,149).…”
Section: Autophago(lyso)somesmentioning
confidence: 99%
“…This resource management system, otherwise known as autophagy, helps maintain homeostasis and can promote cell survival during stress (147). Several studies investigating a role for autophagy during necroptotic signaling have showed increased lipidated LC3 (microtubuleassociated proteins 1A/1B light chain 3B) and other markers of autophagosomes during TNF-induced necroptosis (119,136,148,149). However, this accumulation of autophagosomes is not thought to be due to the stimulation of autophagy during necroptosis but rather due to a failure of autophagosomes to undergo proper lysosomal degradation (119,149).…”
Section: Autophago(lyso)somesmentioning
confidence: 99%
“…Similarly, necroptosis may promote or repress autophagy, although the mechanisms are still unclear [ 80 ]. For example, necroptotic stimulation seems to reduce autophagic activity, as shown by the enlarged puncta of the autophagic substrate Sequestosome 1 (SQSTM1/p62) and its increased colocalization with microtubule-associated protein 1A/1B-light chain 3 (LC3), attenuating autophagic flux before the lysosome fusion step [ 81 ]. The activation of necroptosis in mouse dermal fibroblasts and HT-29 human colorectal cancer cells results in the accumulation of the autophagic marker, lipidated LC3B, in an MLKL-dependent manner.…”
Section: Interplay Between Necroptosis Apoptosis Pyroptosis and mentioning
confidence: 99%
“…Similarly, necroptosis may promote or repress autophagy, although mechanisms are still unclear [75]. For example, necroptotic stimulation has been shown to reduce autophagic activity, as evidenced by enlarged puncta of the autophagic substrate Sequestosome 1 (SQSTM1/p62) and its increased colocalization with microtubule-associated protein 1A/1B-light chain 3 (LC3), attenuating autophagic flux before the lysosome fusion step [76 ]. Activation of necroptosis in mouse dermal fibroblasts and HT-29 human colorectal cancer cells results in accumulation of the autophagic marker, lipidated LC3B in an MLKL-dependent manner.…”
Section: Interplay Between Necroptosis Apoptosis and Autophagymentioning
confidence: 99%